Tanggung Jawab Pemerintah dalam Pemenuhan Hak Masyarakat Adat Pasca Undang-Undang Cipta Kerja - Muhammad Syammakh Daffa Alghazali; Abdhy Walid Siagian; Habib Ferian Fajar (Jurnal Hukum Lex Generalis, 2023)
The fulfillment and recognition of indigenous peoples are in line with the human rights contained in the 1945 Constitution of the Republic of Indonesia. 11 of 2020 concerning Job Creation seems to be a legal umbrella for the legitimacy of indigenous peoples' rights by basing it on Article 33 of the 1945 Constitution of the Republic of Indonesia and TAP MPR RI Number IX/2001 concerning Agrarian Reform and Natural Resource Management. The government's responsibility is to provide certainty on the recognition, protection, and fulfillment of the rights of indigenous peoples until now have not been fulfilled by the state. This is contrary to the constitutional mandate as stated in Article 18B paragraph (2) of the Constitution of the Republic of Indonesia.